MENGATASI KESULITAN PEMBELAJARAN PKN MENGGUNAKAN MODEL PBL DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK KELAS 4 PADA PEMBELAJARAN PKN DI SD - Mudita Pramesti; Yuzevira Nova Ariviana; Kurotul Aeni; Wulan Aulia Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to explore the implementation of the problem-based learning model in enhancing students' understanding. The study adopts a qualitative descriptive approach, used to depict and interpret the meaning of the collected data. The research population comprises all fourth-grade students in one of the public elementary schools in Semarang City for the academic year 2023/2024. The sample consists of 26 fourth-grade students. The instruments used include pre-test and post-test sheets. Based on the research findings, the pre-test results show an average score of 51.4, with an unsatisfactory percentage of 100%. Meanwhile, the post-test results exhibit an average score of 80.9, with a satisfactory percentage of 73%. Consequently, it can be concluded that the implementation of the problem-based learning model is effectively applied in the Civics (PPKn) learning process, specifically in the material related to the formulation process of Pancasila, for fourth-grade students in one of the public elementary schools in Semarang City for the academic year 2023/2024. Through data analysis and student learning outcomes, it is evident that the implementation of the problem-based learning model enhances student understanding.